The giant outburst of EXO 2030+375: I. Spectral and pulse profile evolution - Thalhammer, Philipp; Ballhausen, R.; Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Zainab, Aafia; Staubert, R.; Pottschmidt, K.; Coley, Joel B.; Rothschild, R. E.; Jaisawal, G. K.; West, B.; Becker, P. A.; et al. (Astronomy & Astrophysics, 2024)
The Be X-ray binary EXO 2030+375 went through its third recorded giant outburst from June 2021 to early 2022. We present the results of both spectral and timing analysis based on NICER monitoring, covering the 2-10 keV flux range from 20 to 310 mCrab. Dense monitoring with observations carried out about every second day and a total exposure time of 160 ks allowed us to closely track the source evolution over the outburst. Changes in the spectral shape and pulse profiles showed a stable luminosity dependence during the rise and decline. The same type of dependence has been seen in past outbursts. The pulse profile is characterized by several distinct peaks and dips. The profiles show a clear dependence on luminosity with a stark transition at a luminosity of 2 × 1036 erg s-1, indicating a change in the emission pattern. Using relativistic raytracing, we demonstrate how anisotropic beaming of emission from an accretion channel with a constant geometrical configuration can give rise to the observed pulse profiles over a range of luminosities.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Stars: neutron; X-rays: binaries; X-rays: individuals: EXO 2030+375